Performance Analysis of Various Path Planning Algorithms for the Reliable Navigation of Unmanned Ground Vehicles - Gurpreet Singh (International Journal of Intelligent Systems and Applications in Engineering, 2021)
Unmanned Ground Vehicles (UGV) provides a major boom in the area of vehicular technology by making it safer, fast, reliable and trouble-free. The navigation of UGV is associated with three major segments that are mapping, localization and path planning. This research work is primarily focused on developing a time efficient path planning technique to achieve reliable autonomous navigation of UGV. A number of path planning techniques had been examined and implemented in the past to achieve reliable navigation of UGV but still the optimality in the path planning has not been achieved. In this research, various path planning techniques such as A*, D*, Breadth First Search (BFS) and Orthogonal Jump Point Search (OJPS) are experimentally analyzed based on different parameters in simulator and in real world experiments. This research paper provides a simulation based performance analysis of the path planning techniques based on various parameters such as path length, computational time, number of operations required and trajectory analysis. Based on the performance analysis and the results obtained by performing experiments, A* turns comes out as better option for path planning in complex environment. The trajectory selected by the A* still suffer from path smoothness which is removed by B Spline method that reduce the time lag by 9.87% by reducing the number of sharp turns w.r.t conventional approaches.